7Li in situ 1D NMR imaging of a lithium ion battery. Issue 6 (12th January 2015) - Klamor, S.; Zick, K.; Oerther, T.; Schappacher, F. M.; Winter, M.; Brunklaus, G.
Abstract : The spatial distribution of charge carriers in lithium ion batteries during current flow is of fundamental interest for a detailed understanding of transport properties and the development of strategies for future improvements of the electrolyte–electrode interface behaviour. Abstract : The spatial distribution of charge carriers in lithium ion batteries during current flow is of fundamental interest for a detailed understanding of transport properties and the development of strategies for future improvements of the electrolyte–electrode interface behaviour. In this work we explored the potential of 7 Li 1D in situ NMR imaging for the identification of concentration gradients under constant current load in a battery cell. An electrochemical cell based on PTFE body and a stack of glass microfiber discs that are soaked with a technically relevant electrolyte suitable for high-temperature application and squeezed between a Li metal and a nano-Si–graphite composite electrode was assembled to acquire 7 Li 1D in situ NMR profiles with an improved NMR pulse sequence as function of time and state of charge, thereby visualizing the course of ion concentration during charge and discharge. Surface localized changes of Li concentration were attributed to processes such as solid electrolyte interphase formation or full lithiation of the composite electrode. The method allows the extraction of lithium ion transport properties.